The perception of adolescents about alcohol and other drugs in the family context - Pereira, Maria Odete; Silva, Silvio Silvério da; Oliveira, Márcia Aparecida Ferreira de; Vargas, Divane; Colvero, Luciana de Almeida; Leal, Bianca Mara Maruco Lins (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2011)
The consumption of alcohol and other drugs is increasingly frequent among adolescents. The study aimed to identify the perception of adolescents about the consumption of alcohol and other drugs within the family. In this qualitative study, focus groups were used to collect data. The five collaborators, between 12 and 15 years old, attended a social service center affiliated with a higher education institution in a city in the Médio Vale do Paraíba Paulista. The reports expressed the adolescents' perception, its contradictions and feelings on the theme and this perception was based on family members' habits.